Diagnostic Significance of d.Xylose Excretion Test. Issue 1 (March 1960) - Fowler, D.; Cooke, W. T.
Abstract : This paper assesses the use of d.xylose as a test of function of the small intestine. In general d.xylose excretion is associated with disturbance of the intestinal wall of the upper jejunum. Low readings are found with adult coeliac disease but rarely with regional enteritis.